Purchasing sex in Sweden—a risky business - Grönvall, Ylva (The British journal of criminology, 2022)
This article is based on a study exploring how men who purchase sex in Sweden experience and navigate risk. The focus is on individual assessments of risk in relation to experiences of crime, exploitation and stigma. Based on interviews with 30 Swedish men who purchase sex, an inductive thematic analysis has been applied. The participating men had different strategies to avoid crime and exploitation and they navigated in relation to stigma when purchasing sex. Their risk assessments and conceptualizations of purchasing sex were based on own experiences and on the normative discourse on commercial sex in Sweden. Their fields of action were structured through discipline, governing and responsibilization, and they tried to distance themselves from being defined as ‘sex buyers’ and to purchase sex in ‘good’ ways.